Radical Hysterectomy Plus Concurrent Chemoradiation/Radiation Therapy Is Negatively Associated With Return to Work in Patients With Cervical Cancer. Issue 1 (January 2017) - Nakamura, Keiichiro; Masuyama, Hisashi; Ida, Naoyuki; Haruma, Tomoko; Kusumoto, Tomoyuki; Seki, Noriko; Hiramatsu, Yuji
Abstract : Objective: Cervical cancer is one of the most common malignant diseases in working-age women. This study investigated the influence of adverse effects of various treatment modalities on return to work in women with cervical cancer. Methods: Questionnaires and clinical data from medical records of 97 patients with early stage (stages I and II) cervical cancer were collected and assessed by treatment received. The following treatment groups were analyzed for correlations between time to return to work and various adverse effects: radical hysterectomy (RH) alone, RH group (n = 29); concurrent chemoradiation therapy (CCRT)/radiation therapy (RT) alone, CCRT/RT group (n = 21); and RH + CCRT/RT group (n = 47). The χ 2 test was used to determine the significance of the correlations. Results: The mean age at the time of diagnosis was 43.0 years and the average interval since treatment was 4.5 years. The RH + CCRT/RT group was the most strongly negatively associated with return to work in employed patients who had undergone CCRT/RT group of cervical cancer ( P = 0.012). There was a significant association between failure to return to work and lower extremity lymphedema ( P = 0.049). A more than–6-month interval between treatment and return to work and reduced personal income occurred in a significantly higher percentage of patients in the RH + CCRT group than in the CCRT/RT group ( P = 0.034 and P = 0.034). Conclusions: Of the treatments assessed, RH + CCRT/RT has the greatest negative effect on return to work in women with cervical cancer.